2010
DOI: 10.1021/es102785d
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A (BPA) in U.S. Food

Abstract: Bisphenol A (BPA) is a chemical used for lining metal cans and in polycarbonate plastics, such as baby bottles. In rodents, BPA is associated with early sexual maturation, altered behavior, and effects on prostate and mammary glands. In humans, BPA is associated with cardiovascular disease, diabetes, and male sexual dysfunction in exposed workers. Food is a major exposure source. We know of no studies reporting BPA in U.S. fresh food, canned food, and food in plastic packaging in peer reviewed journals. We mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
2
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(185 citation statements)
references
References 47 publications
6
171
2
6
Order By: Relevance
“…23 Several previous studies have reported that BPA in the inner coating of cans may leach into the food based on measurements of BPA concentrations in various canned products. [24][25][26][27][28][29] BPA concentrations in the canned beverage in the present study were comparable with the results of previous studies. For instance, Lim et al 26 reported that mean BPA concentrations in canned beverages were 8.30 μg/kg, with the range being nondetectable to 14.26 μg/kg.…”
Section: Discussionsupporting
confidence: 92%
“…23 Several previous studies have reported that BPA in the inner coating of cans may leach into the food based on measurements of BPA concentrations in various canned products. [24][25][26][27][28][29] BPA concentrations in the canned beverage in the present study were comparable with the results of previous studies. For instance, Lim et al 26 reported that mean BPA concentrations in canned beverages were 8.30 μg/kg, with the range being nondetectable to 14.26 μg/kg.…”
Section: Discussionsupporting
confidence: 92%
“…It is known that epoxy resins used as liners for metal cans release bisphenol A (BPA) into canned foods. Elevated concentrations of BPA have been reported in canned foods (Cao et al, 2010;Noonan et al, 2011;Schecter et al, 2010). Our results suggest that there is no association between the concentration of parabens in foods and Vegetables and fruits include fresh and processed products; cereals include cereal products.…”
Section: Comparisons Among Food Categoriesmentioning
confidence: 54%
“…For example, the polyphenolic compound bisphenol A, which is used as a plasticizer in can linings, has been detected in canned cat food and may act as a thyroid disruptor (Edinboro et al 2004, Schecter et al 2010. In a similar vein, recent studies both in the USA and Sweden have reported high levels of polybrominated diphenyl ethers (PBDEs) in cats, a fire-retardant with known thyroid-disrupting properties (Dye et al 2007, Guo et al 2012, Mensching et al 2012, Norrgran et al 2012.…”
Section: Why Has Feline Nodular Goiter Reached Such Epidemic Proportimentioning
confidence: 99%